Evaluation of the Antinutrients, Amino Acid Profile and Physicochemical Properties of Hura crepitan Seed - E. C. Nwokenkwo; J. N. Nwosu; N. C. Onuegbu; I. A. Olawuni; A. F. Ofoedum (Archives of Current Research International, 2020)
The Objectives of the Study: To evaluate the Antinutritional components, Amino acid profiles and the physic-chemical properties of Hura crepitan (Sand box) seed. Design of the Study: This study was structured to fit into using a combination of T-test and one way Analysis of Variance (ANOVA) to evaluate the data obtained from the laboratory analysis. Place and Duration of Study: This research work was done at the Department of Food Science and Technology Laboratory, Federal University of Technology, Owerri, Nigeria, between May 2019 and November 2019. Methods: The mature dry fruits of the Hura crepitan seeds were harvested from the plants on Federal University of Technology Owerri, Imo State campus. The Hura crepitan seeds were sorted in order to remove dirts and foreign other foreign contaminants. The cleaned seeds were divided into four portions and stored in separate glass containers for further processing. The first portion of the seeds were dried at 60°C in Gallen Kamp moisture extraction oven for 6 hours at and pulverised in a Monilex blended into flour, some seeds were boiled while some portions were roasted and processed into fine flour and subsequently subjected to analysis to evaluate the antinutritional contents, amino acid s as well as determining the physic-chemical properties of the samples. Results: The results obtained suggested that the anti-nutrients in the raw seed-flour were flavonoids with 17.50%, alkaloid (6.20%), tannin (5.24%), and cyanogenic glycoside (1.76%). Fermentation and moist cooking were found to be more effective in the reduction of the anti-nutrients in the Hura crepitan seeds. The amino acid profiles were evaluated, and twenty amino acids were identified in the seed flour. The three major ones implicated were arginine (3.25 g/100 g in cooked and 8.05 g/100 g in fermented), glutamic acid (6.05 g/100 g in cooked and 10.2 g/100 g in fermented) and valine (8.03 g/100 g in raw and 8.58 g/100 g in fermented). The limiting amino acid is methionine with a chemical score of 44.52%. the physicochemical properties of the sandbox seeds evaluated suggested that the free fatty acids values ranged from 3.60% to 6.03% and there were no significant differences (P>0.05) among the samples, the iodine value ranged from 104.94% to 126.90%, the peroxide value for the sample varies between 2.96% to 44.81%. Conclusion: This study suggested that the Hura crepitan seed contains appreciable amounts of essential amino acids as well as having good physicochemical properties while the use of moist heat and/or fermentation can reduce the antinutritional components to the bearest minimum. Hence, can be utilized some areas of food industries where protein (amino acids) are critically required.